Cartilage-on-cartilage contact: effect of compressive loading on tissue deformations and structural integrity of bovine articular cartilage. Issue 12 (December 2018) - Zevenbergen, L.; Gsell, W.; Cai, L.; Chan, D.D.; Famaey, N.; Vander Sloten, J.; Himmelreich, U.; Neu, C.P.; Jonkers, I.
Summary: Objective: This study aims to characterize the deformations in articular cartilage under compressive loading and link these to changes in the extracellular matrix constituents described by magnetic resonance imaging (MRI) relaxation times in an experimental model mimicking in vivo cartilage-on-cartilage contact. Design: Quantitative MRI images, T 1, T 2 and T 1 ρ relaxation times, were acquired at 9.4T from bovine femoral osteochondral explants before and immediately after loading. Two-dimensional intra-tissue displacement and strain fields under cyclic compressive loading (350N) were measured using the displacement encoding with stimulated echoes (DENSE) method. Changes in relaxation times in response to loading were evaluated against the deformation fields. Results: Deformation fields showed consistent patterns among all specimens, with maximal strains at the articular surface that decrease with tissue depth. Axial and transverse strains were maximal around the center of the contact region, whereas shear strains were minimal around the contact center but increased towards contact edges. A decrease in T 2 and T 1 ρ was observed immediately after loading whereas the opposite was observed for T 1 . No correlations between cartilage deformation patterns and changes in relaxation times were observed. Conclusions: Displacement encoding combined with relaxometry by MRI can noninvasively monitor the cartilage biomechanical and biochemical properties associated with loading. The deformation fields reveal complex patterns reflecting the depth-dependent mechanical properties, but intra-tissue deformation under compressive loading does not correlate with structural and compositional changes. The compacting effect of cyclic compression on the cartilage tissue was revealed by the change in relaxation time immediately after loading.